Clinical Approaches for Understanding the Expression Levels of Pattern Recognition Receptors in Otitis Media with Effusion - So Yoon Lee (Clinical and Experimental Otorhinolaryngology, 2011)
ObjectivesBacterial infections in the normally sterile environment of the middle ear cavity usually trigger host immune response, whereby the innate immune system plays a dominant role as the host's first line of defense. We evaluated the expression levels of Toll-like receptors (TLRs) -2, -4, -5, -9, and nucleotide-binding oligomerization domain-containing proteins (NODs) -1 and -2, all of which are related to bacterial infection in pediatric patients with otitis media with effusion (OME).MethodsThe study sample consisted of 46 pediatric patients with OME, all of whom had ventilation tubes inserted. The expression levels of TLR-2, -4, -5, -9, NOD-1 and -2 mRNA in middle ear effusion were assessed by polymerase chain reaction (PCR). Difference of pattern recognition receptors (PRRs) expression level by presence of bacteria, ventilation tube insertion rate, and effusion fluid character was assessed.ResultsAll effusion fluid samples collected from patients with OME showed expression of TLR-2, -4, -5, -9, NOD-1, and -2 mRNA by PCR. However, we found no differences among expression levels of PRRs in relation to characteristics of exudates, presence of bacteria, or frequencies of ventilation tube insertion (P>0.05).ConclusionOur findings suggest that exudates of OME patients show PRR expressions that are related to the innate immune response regardless of the characteristics of effusion fluid, presence of bacteria in exudates, or frequency of ventilation tube insertion.